El estatuto jurídico de las fuerzas armadas - López de Gea, Joaquín (Revista de Derecho de la UNED (RDUNED), 2013)
The 8th article of the Spanish Constitution lists the missions of the Armed Forces. These Armed Forces are an Administration with special features relative to personnel legal regulations, operative procedures, values, targets and purposes. This article tries to go through the Army legal regulations, underlining the analysis of its nature and missions in order to update the current legal literature. To sum it up, a big addition of missions to the «status quo» of the Armed Forces recently happened, brought as a result of the international integration of Spain; and, secondly, the Armed Forces may be considered as an «institutional Administration». El artículo 8 de la Constitución Española enumera las misiones de las Fuerzas Armadas. Éstas constituyen una Administración con singularidades en materia de régimen de personal, procedimientos operativos, valores, objetivos y funciones. En el presente artículo revisamos, con ánimo de actualizar la literatura jurídica existente, el régimen jurídico de las Fuerzas Armadas, poniendo especial énfasis en el análisis de su naturaleza y de sus misiones. De ello concluimos, una gran ampliación de éstas últimas, fruto de la incorporación de España a la esfera internacional y en segundo lugar, la configuración de una naturaleza administrativa con connotaciones institucionales.